Flexible Working Arrangement toward Organizational Commitment and Work-Family Conflict - Lee, Jasmine Mee Choo; Desa, Nasina; Asaari, Muhammad Hasmi Abu Hassan (Universiti Sains Malaysia, 2016)
The purpose of this paper is to examine the relationship between flexible working arrangements and organizational commitment and work-family conflict. A total of 130 questionnaires were distributed to the finance executives and the returned yielding a response rate of 87%. The results revealed that a flexible working arrangement was significantly and positively related to organizational commitment. It also revealed that a flexible working arrangement was significantly and positively related to work-family conflict. Theoretically, this paper has contributed to the literature on the flexible working arrangement and organizational commitment. Practically, the practitioners of manufacturing companies should consider implementing flexible working policies to cater to the needs of their employees by providing flexi-time, remote working or different working hours. In conclusion, this paper has revealed the importance of flexible working arrangement policies in affecting organizational commitment and work-family conflict.